Contribution of NKT cells and CD1d-expressing cells in obesity-associated adipose tissue inflammation - Satoh, Masashi; Iwabuchi, Kazuya (Frontiers in Immunology, 2024)
Natural killer T (NKT) cell are members of the innate-like T lymphocytes and recognizes lipid antigens presented by CD1d-expressing cells. Obesity-associated inflammation in adipose tissue (AT) leads to metabolic dysfunction, including insulin resistance. When cellular communication is properly regulated among AT-residing immune cells and adipocytes during inflammation, a favorable balance of Th1 and Th2 immune responses is achieved. NKT cells play crucial roles in AT inflammation, influencing the development of diet-induced obesity and insulin resistance. NKT cells interact with CD1d-expressing cells in AT, such as adipocytes, macrophages, and dendritic cells, shaping pro-inflammatory or anti-inflammatory microenvironments with distinct characteristics depending on the antigen-presenting cells. Additionally, CD1d may be involved in the inflammatory process independently of NKT cells. In this mini-review, we provide a brief overview of the current understanding of the interaction between immune cells, focusing on NKT cells and CD1d signaling, which control AT inflammation both in the presence and absence of NKT cells. We aim to enhance our understanding of the mechanisms of obesity-associated diseases.